2023
DOI: 10.3390/cancers15030924
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinthin Expression Is Associated with Poor Prognosis in Patients with Non-Small-Cell Lung Cancer

Abstract: To determine Labyrinthin (LAB) expression in non-small-cell lung cancer (NSCLC), we immunostained and scored for LAB immunohistochemistry (IHC) expression on sections of tissue microarrays (TMAs) prepared from 256 archival tissue blocks of NSCLC. Propensity-score-weighted Kaplan–Meier curves and weighted Cox models were used to associate LAB expression with overall survival. LAB mRNA expression was assessed in The Cancer Genome Atlas (TCGA) and correlated with clinical phenotype and outcome. Positive LAB IHC e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In patients with metastatic NSCLC under PD-1 inhibitors treatment, serum lactate dehydrogenase and C-reactive protein concentrations were significantly associated with overall survival 32 . In a recent study, the expression of labyrinthin, a novel cancer neoantigen, was suggested to be associated with prognosis in NSCLC patients 33 . Moreover, the elevated transcription of CPEB4, or IRF4, in peripheral blood was associated with poor survival 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with metastatic NSCLC under PD-1 inhibitors treatment, serum lactate dehydrogenase and C-reactive protein concentrations were significantly associated with overall survival 32 . In a recent study, the expression of labyrinthin, a novel cancer neoantigen, was suggested to be associated with prognosis in NSCLC patients 33 . Moreover, the elevated transcription of CPEB4, or IRF4, in peripheral blood was associated with poor survival 34 .…”
Section: Discussionmentioning
confidence: 99%
“…LAB expression is an independent poor prognostic factor for LUAD. 1 High prevalence of LAB expression was also found in breast cancer samples (95.8%, 93/97). There was no significant difference in the LAB expression among the ER, PR, and HER2 positive subgroups.…”
mentioning
confidence: 89%
“…IHC assay was used to detect LAB expression on 11 out of 12 (91.7%) patients screened for the phase I trial. Tumor origins included colon or rectum (8), ovarian (1), scalp (1), and prostate (1). LAB RNA was expressed in both oncogene-driven and nononcogene-driven adenocarcinomas.…”
mentioning
confidence: 99%